2007
DOI: 10.1007/s11605-007-0140-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Preoperative Peripheral Blood Monocyte Count in Patients with Colorectal Liver Metastasis after Liver Resection

Abstract: Prognostic values of leukocyte subset counts in peripheral blood of cancer patients have not yet been fully investigated. We retrospectively examined the relation between preoperative absolute counts of peripheral blood leukocyte subsets and clinicopathologic factors and long-term prognosis in 97 patients with liver metastasis from colorectal cancer who underwent hepatic resection. Median preoperative peripheral blood leukocyte subset counts were as follows: neutrophils 3148/mm3; lymphocytes 1574/mm3; monocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 28 publications
1
48
0
2
Order By: Relevance
“…Recently, Schmidt et al reported that pretreatment levels of peripheral neutrophils are independent predictors of overall survival in patients with stage IV Melanoma [23] and this finding was also found in a Japanese study group in advanced non-small-cell lung cancer [24]. In colorectal cancers, peripheral monocyte count is the only independent prognostic biomarker for survival, not neutrophil or lymphocyte counts [25,26]. Because it is unclear whether these conflicting results are due to tumor-specific phenomena or the tumor burden itself (for example advanced vs. early stage), further study is warranted.…”
Section: Discussionmentioning
confidence: 81%
“…Recently, Schmidt et al reported that pretreatment levels of peripheral neutrophils are independent predictors of overall survival in patients with stage IV Melanoma [23] and this finding was also found in a Japanese study group in advanced non-small-cell lung cancer [24]. In colorectal cancers, peripheral monocyte count is the only independent prognostic biomarker for survival, not neutrophil or lymphocyte counts [25,26]. Because it is unclear whether these conflicting results are due to tumor-specific phenomena or the tumor burden itself (for example advanced vs. early stage), further study is warranted.…”
Section: Discussionmentioning
confidence: 81%
“…A correlation between monocytosis and poor prognosis in different types of cancer has previously been observed (16,(25)(26)(27). Monocytes represent a source of chemokines and cytokines that contribute to inflammation (28).…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 89%
“…Some investigators have explored a relation between pretreatment SAL and/or preoperative peripheral ABCC, and prognosis in patients with locally advanced and metastatic CRC [18,23,[28][29][30][31][32][33] . These studies have been based on mixed populations with tumors located in various parts of the large bowel including the rectum.…”
Section: Discussionmentioning
confidence: 99%